Determinant of Quality of Work Life (QWL) and its Impact on Staff Job Satisfaction in Nepalese Organizations - Paudel, Manoj (Journal of Entrepreneurship & Management Studies, 2024)
The purpose of this study was to investigate and analyze the many aspect of quality of work life in different organizations in the context of Nepal. For this, the study was carried out using positivist prospective as this allows the researcher for the development of hypotheses based on established theories. A causal-comparative study design was employed to establish the causes and effects of particular variables. Using series of structural questionnaires, information was obtained from 415 Staff who were employed in different organizations and different job roles in order to collect the primary data. Multiple regression, f-test, mean, and standard deviation were used in the studies.The study showed that work and workplace, reward and benefits and organizational process and culture were found statistically significant.